A case of stroke secondary to iron deficiency anemia in a young female patient - Anilkumar, Devika; Periyasamy, Manimekalai; Vinatha, Mullangi Chenchu; Alex, J. (International Journal of Advances in Medicine, 2022)
In this article, we are reporting a case of acute stroke that occurred in a young patient with iron deficiency anaemia (IDA). There are only a few cases where the association between IDA and stroke has been established. The possible mechanisms behind the relation between IDA and stroke are anaemic hypoxia-induced to the brain, hypercoagulable state secondary to IDA and thrombocytosis secondary to IDA. In this patient, all causes of stroke were ruled out except Iron deficiency anaemia which came out to be the reason for the stroke. A decrease in the amount of haemoglobin in the blood results in decreased oxygen supply to the brain, causing hypoxia to the brain. This, in turn, leads to ischemic stroke. Therefore, diagnosing anaemia in patients and starting treatment as early as possible is important.